Multisensory flavor perception: Assessing the influence of fruit acids and color cues on the perception of fruit-flavored beverages - Zampini, M; Wantling, E; Phillips, N; Spence, C (2008)
We report a study designed to investigate the influence of fruit acids (in particular, citric and malic acid) on people's perception of the identity and the intensity of a variety of different fruit-flavored solutions. Participants had to identify the flavor of fruit-flavored drinks that were colored yellow, grey, orange, red, or else were presented as colorless solutions. The participants also rated the intensity of flavor, sweetness, and sourness of each solution using a Labelled Magnitude Scale (LMS). The participants identified the flavors of the beverages more accurately when citric and malic acids were added to the solutions, and/or when the solutions were colored appropriately. Moreover, the perception of flavor intensity was modulated by the presence of the fruit acids in the solutions. © 2007 Elsevier Ltd. All rights reserved.